Pengembangan Pembelajaran Bahasa Inggris di Madrasah Jamiyatut Tholibin Desa Soket Dajah Bangkalan Madura - Roidatus Shofiyah; Siti Nurul Fatimah Tarimana (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This article discusses the English language learning development program at Madrasah Jamiyatut Tholibin, Soket Dajah Village, Bangkalan, Madura. This program was motivated by the low English language skills of students in the area, which were caused by limited educational facilities, lack of teaching resources, and ineffective teaching methods. This program aims to improve students' English skills through a more interactive and contextual approach, which is relevant to their daily lives. In addition, this program also involves training for teachers to improve their competence in teaching English, including the use of media and technology as learning aids. The results of this program showed a significant increase in students' English skills, both in terms of comprehension and communication skills. In addition, this program also succeeded in increasing students' learning motivation and developing teachers' capacity in teaching English. Thus, this program is expected to be a model for the development of English language learning in other rural areas in Indonesia.